Hierarchy of Needs in Angie Thomas’s Novel "The Hate U Give": Abraham Maslow - Nursaamah Lubis; Robby Satria (Humanitatis : Journal of Language and Literature, 2021)
This research discusses hierarchy of needs in the novel "The Hate U Give" by Angie Thomas (2017) as the data source and using a psychological approach. In this research, researcher focused on what are the hierarchical needs in the novel "The Hate U Give" by Angie Thomas (2017). This research used descriptive qualitative by Creswell (2013) to analyze and with Maslow (1987) theory’s of hierarchy of needs. The phenomenon of hierarchy of needs reflected in this novel occurred in Mississippi, America in 2010. This research shows the influence of hierarchy of needs experienced by the characters in the novel "The Hate U Give" by Angie Thomas (2017) such as; Physiological, Safety, Love/ belonging, Esteem, Self-actualization.